PEMBELAJARAN MENULIS TEKS DRAMA MENGGUNAKAN PENDEKATAN DEDUKTIF BERBANTUAN APLIKASI WATTPAD - Sony Harsono; Wikanengsih Wikanengsih; Dida Firmansyah (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2020)
This research is motivated by improved learning quality and learning should be student-centered, the observation of KBM obtained the value of students are not satisfactory and the interest of learners in writing less. The purpose of this research is to measure the quality of learning through the value of learners in drama text learning, as well as to know the interest of learners in writing learning, especially writing drama text using deductive approach with apalication Wattpad. The research methods used are qualitative descriptive.  The population in this study was 70 students of Grade VIII SMP Negeri 3 Cisarua. Sampling uses random sampling, obtained by Class VIII B as a sample in this study, as many as 20 students. The results earned the highest value student value of 92, the lowest value of 50 and the average value of 76.25. Students have a high interest in writing the drama text proved with the results of a student poll of 2.99 entry on either qualification high. It can be concluded that once given a tretment using the assisted deductive approach of Wattpad application, the value of learners satisfactorily and learners to have an interest in writing drama text.